The Twin Cycle Hypothesis of type 2 diabetes aetiology: From concept to national NHS programme - Roy Taylor (Experimental Physiology, 2025)
Abstract The development of magnetic resonance methods for quantifying intra‐organ metabolites has permitted advances in the understanding of fasting and post‐prandial carbohydrate and lipid handling in people with and without type 2 diabetes. Insulin resistance in the liver was shown to be related to excess intra‐organ fat and was able to be returned to normal by weight loss. The practical effect of having muscle insulin sensitivity in the lower part of the wide normal range resulted in the obligatory shunting of carbohydrates via de novo lipogenesis into saturated fat. These observations provided the basis for the Twin Cycle Hypothesis of the aetiology of type 2 diabetes. Subsequent studies on people with type 2 diabetes confirmed the postulated pathophysiological abnormalities and demonstrated their reversibility by dietary weight loss of 10–15 kg. Overall, the fundamental understanding of the mechanisms causing type 2 diabetes has bridged physiological and clinical perspectives. Large population‐based randomised controlled trials confirmed the practical clinical application of the method of achieving substantial weight loss, and an NHS programme is now in place offering potential remission to people within 6 years of diagnosis.